Epicardial fat density, coronary artery disease and inflammation in people living with HIV. Issue 9 (3rd March 2023) - Sadouni, Manel; Duquet-Armand, Marie; Alkeddeh, Mohamed Ghaiss; El-Far, Mohamed; Larouche-Anctil, Etienne; Tremblay, Cécile; Baril, Jean-Guy; Trottier, Benoit; Chartrand-Lefebvre, Carl; Durand, Madeleine; ,
Abstract : Studies have shown an increased risk of coronary artery disease (CAD) in the human immunodeficiency virus (HIV) population. Epicardial fat (EF) quality may be linked to this increased risk. In our study, we evaluated the associations between EF density, a qualitative characteristic of fat, and inflammatory markers, cardiovascular risk factors, HIV-related parameters, and CAD. Our study was cross-sectional, nested in the Canadian HIV and Aging Cohort Study, a large prospective cohort that includes participants living with HIV (PLHIV) and healthy controls. Participants underwent cardiac computed tomography angiography to measure volume and density of EF, coronary artery calcium score, coronary plaque, and low attenuation plaque volume. Association between EF density, cardiovascular risk factors, HIV parameters, and CAD were evaluated using adjusted regression analysis. A total of 177 PLHIV and 83 healthy controls were included in this study. EF density was similar between the two groups (−77.4 ± 5.6 HU for PLHIV and −77.0 ± 5.6 HU for uninfected controls, P = .162). Multivariable models showed positive association between EF density and coronary calcium score (odds ratio, 1.07, P = .023). Among the soluble biomarkers measured in our study, adjusted analyses showed that IL2Rα, tumor necrosis factor alpha and luteizing hormone were significantly associated with EF density. Our study showed that an increase in EF density was associated with a higher coronary calcium score and with inflammatory markers in a population that includes PLHIV.